The Impact of Renewable Energy, CO2 Emissions, and Population on Economic Growth in ASEAN 2013-2023 - Syarifah (Outline Journal of Economic Studies, 2026)
Purpose: This study investigates how renewable energy consumption, CO₂ emissions, and population size influence economic growth in selected ASEAN countries Indonesia, Malaysia, Thailand, the Philippines, and Vietnam over the period 2013–2023. It aims to provide insights into the role of environmental and demographic factors in achieving sustainable economic development. Methods: The research employs panel data regression analysis, utilizing both Fixed Effects Model (FEM) and Random Effects Model (REM). The Hausman test is applied to determine the most appropriate model for estimation, ensuring robust and reliable results across the dataset. Results: The findings reveal that renewable energy consumption has a positive and statistically significant effect on economic growth. In contrast, CO₂ emissions negatively impact economic performance, indicating environmental degradation may hinder growth. Population size shows a generally positive influence, although its effect varies across countries and periods. Conclusions: The study emphasizes the importance of expanding renewable energy use and implementing effective emission control policies to foster sustainable growth. Policymakers should balance economic expansion with environmental preservation. Originality: This research offers updated panel evidence from ASEAN economies, integrating environmental and demographic variables within a decade-long analysis.